EFEKTIVITAS METODE DRILL UNTUK MENINGKATKAN PEMAHAMAN MENULIS HURUF HIJAIYYAH BRAILLE MELALUI PAPAN REGLET PADA SISWA TUNANETRA KELAS 2 - Budiono Budiono (Universitas Negeri Padang, 2018)
This study aims to determine the effectiveness of the Drill method to improve the understanding of writing hijaiyyah letters through a reglet board on students with visual impairments in grade 2 at SDLB Putra Manunggal Gombong, Kebumen. This research is a classroom action research with 4 students of SDLB Putra Manunggal Gombong as the research subjects. This study consisted of 2 cycles that each cycle has three times of meetings. The utilized instruments were test sheet, interview sheet, and observation sheet. Triangulation techniques was used to validate the data. The results showed that: (1) the Drill method was effective in improving students ability to write hijaiyyah braille letters and that achieved a good category; (2) the understanding of writing hijaiyyah letters of SDLB students was increased through Drill method. They achieved an average value in the first cycle by number 64.66 with 50% learning completeness whereas in the second cycle was 72.34 with 75% learning completeness.Keywords: effectiveness, Drill method, writing comprehension, Reglet board